Tips for remarkable hospitality: communicating effectively with the VVIP / Aida Khalida Mohamed Idris and Dr. Suria Sulaiman - Mohamed Idris, Aida Khalida; Sulaiman, Suria (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2025)
On the 28th of June 2024, the class of PHM2403A were delighted to have the opportunity on having firsthand knowledge from the communications maestro, En. Kamarul Baharin Haron . As part of the collaborative teaching requirements, the codes involved are HTH 356 (Premier Service), HTH500 (Hospitality Service Management) and HTH 566 (Hotel and Design Layout). It is crucial since the codes involved in teaching good communication between the stakeholder and shareholder in the hospitality industry. En. Kamarul Baharin Haron, for those who might have known or heard of his name is the former Editor-in-Chief and Anchor of Astro Awani of which his best achievements were leading Astro Awani into the digital era and breaking the norms of talk show anchoring culminating in the highest ever live Malaysian TV and online ratings for the 14th GeneraI Election coverage.